Emergency obstetric care: Making the impossible possible through task shifting. (October 2015) - Schneeberger, Caroline; Mathai, Matthews
Abstract: Task shifting—moving tasks to healthcare workers with a shorter training—for emergency obstetric care (EmOC) can potentially improve access to lifesaving interventions and thereby contribute to reducing maternal and neonatal morbidity and mortality. The present paper reviews studies on task shifting for the provision of EmOC. Most studies were performed in Sub-Saharan Africa and South Asia and focused primarily on task shifting for the performance of cesarean deliveries. Cesarean delivery rates increased following EmOC training without significant increase in adverse outcomes. The paper discusses the advantages and disadvantages of task shifting in EmOC and the role of this approach in improving maternal and newborn health in the short and long term.